Effect Skillful Exercises by Playing Method to Developing The Short Anaerobic Ability and Team Attacking for Young Basketball Players - Abbas Hatem Alwan; Tahseen Hamzah Najm (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the research lies in preparing skillful exercises in the method of playing and knowingtheir effect on the anaerobic ability and team attacking of the junior basketball players.As for the research problem: the research problem centered on lack of focus and lack of interest in exercisesthat are built according to the physiological systems that overlap with work (anaerobic) and that would bringabout functional changes that are reflected in the development of the physical, skill and planning aspect inorder to make the player able to bear physical and functional burdens similar to the burdens of competition.The objective of the research was to: Prepare skillful exercises by playing method of basketball, as wellas to identify the effect of skill training by playing method to development the anaerobic ability and teamattacking for young basketball players, and the imposition of the research is: There is an effect of skillfultraining by playing method on anaerobic ability and team attacking for young basketball players.As for the research methodology and its field procedures: the researchers used the experimental method tosolve the research problem, while the research community was identified with the emerging players of AlHillah Basketball Club, and they were distributed into two groups (experimental and control) by a simplerandom method (draw).While the most important conclusions were: that skill exercises by playing method helped to develop(anaerobic ability), and also that skillful exercises by playing method contributed greatly to the developmentof the team attacking of basketball for the young players.As for the most important recommendations, they were: The researchers recommend paying attention tothe use of skillful exercises by playing method according to scientific training bases to raise the efficiencyof anaerobic basketball players during matches and competitions, the researchers recommend attention topreparing and organizing skill exercises by playing method when training the team attacking of basketballin its various types and for all groups.